Goniothalamin isolated from Goniothalamus andersonii improves hematological and biochemical markers in induced leukemia BALB/c mice - Yaacob, Siti M.; Iskandar, Nor H.; Rashid, Zalilawati M.; Johari, Syed A. T. T.; Ismail, Intan S. (Faculty of Pharmacy, University of Benin, 2024)
The efficacy of goniothalamin, a styryl-lactone derivative as an alternative drug for leukemia treatment has generated interest among natural products scientists. However, the studies on goniothalamin treatment effects on serum biochemicals in relation to haematology have been lacking. This study evaluated the effect of goniothalamin (GTN) isolated from Goniothalamus andersonii supplemented into induced leukemia BALB/c mice model to determine the serum biochemicals and hematological markers changes post supplementation. The mice were categorized into normal mice (NM), untreated leukemia (LM) and goniothalamin-treated leukemia (GTN-LM) groups. Treated mice were supplemented with 40 mg goniothalamin per kg b.w. from day-14 and every alternate day until day-28. The present study showed that the enlarged spleen of leukemia mice was reduced toward normal dimension following GTN treatment. Besides, the serum biochemicals related to kidney and liver functions including urea (8.43 ± 0.85 mmol/L), creatinine (20.33 ± 0.67 µmol/L), total bilirubin (1.78 ± 0.17 µmol/L), alanine transaminase (ALT) (65.33 ± 23.51 U/L) and aspartate aminotransferase (AST) (245.00 ± 36.17 U/L) of the GTN-LM group were found to be significantly different than LM group. Conversely, the insignificant difference of these biomarkers between GTN-LM and NM groups had indicated the improvement of leukemia toxicity to normal condition. The GTN-LM peripheral blood containing lower immature granulocytes and monocytes as well as had higher apoptotic index (35%) as compared to LM signified that goniothalamin had induced the apoptotic cell death. Thus, this finding highlighted the potential of goniothalamin as an alternative medicine against leukemia.